The Metaphorical Conceptualization of Political Closure in Post-2021 Iraqi Elections: Newspaper Headlines and Cartoons as a Case Study - Wahaab Jabber, Khalid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The study investigates the concept of “Political Closure,” of post 2021 Iraqi elections. The study explores the verbal, pictorial, and multimodal metaphors of “Political Closure” representation in Iraqi newspaper headlines and cartoons. The data are collected from the Iraqi daily newspapers. The headlines and cartoons are analyzed based on Lakoff & Johnson’s (1980) Conceptual Metaphor theory (CMT). To elicit the pictorial or multimodal metaphors from the cartoons concerning “Political Closure” Forceville’s (1996, 2008) pictorial metaphor is adopted and to determine their kinds. The study revealed that the concept of “political closure” is conceptualized in different source domains; physical object, machine, economic activity, software, code container, building, and illness. The study also revealed that the more frequently kind used to conceive the concept of “Political Closure” is multimodal metaphor since if the textual part is eliminated from the cartoons will result in the disappearance of the metaphorical meaning. Whereas the pictorial metaphor is less used to portray the concept of political closure. DOI: https://doi.org/10.54633/2333-024-057-003